Molecular Docking Study of the C-10 Massoia Lactone Compound as an Antimicrobial and Antibiofilm Agent against Candida tropicalis - Hasyrul Hamzah; Titik Nuryastuti; Widya Rahmah; Lutfi Chabib; Eka Siswanto Syamsul; Dwi Lestari; Asriullah Jabbar; Sylvia Utami Tunjung Pratiwi (The Scientific World Journal)
Antimicrobial resistance is now considered a global health problem because it reduces the effectiveness of antimicrobial drugs. According to the World Health Organization (WHO), the highest mortality rate is associated with infections caused by multidrug-resistant microorganisms, with approximately 700,000 deaths worldwide each year. The aim of this study was to determine the potential of C-10 massoia lactone to inhibit the growth of fungi and C. tropicalis biofilm, and molecular docking studies were performed to determine the nature of the inhibition. The study was conducted using the microdilution method for antifungal and antibiofilm testing and designed with a molecular docking approach. Furthermore, an analysis using the scanning electron microscope (SEM) was performed to evaluate the mechanism of effect. The results obtained showed that C-10 massoia lactone can inhibit the growth of fungi by 84.21% w/v. Meanwhile, the growth of C. tropicalis biofilm in the intermediate phase was 80.23% w/v and in the mature phase was 74.23% w/v. SEM results showed that C-10 massoia lactone damaged the EPS matrix of C. tropicalis so that hyphal formation was hindered due to damage to fungal cells, resulting in a decrease in attachment, density, and lysis of C. tropicalis fungal cells. Based on molecular docking tests, C-10 massoia lactone was able to inhibit biofilm formation without affecting microbial growth, while docking C-10 massoia lactone showed a significant binding and has the potential as an antifungal agent. In conclusion, the C-10 massoia lactone compound has the potential as an antibiofilm against C. tropicalis, so it can become a new antibiofilm agent.